ANALISIS KESALAHAN BERBAHASA PADA ABSTRAK KARYA ILMIAH MAHASISWA: TINJAUAN LITERATURE - Qoshrin Tsaniya Aurellia; Nada Nadia; Yanti Linarsih; Laili Amalia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze errors in the use of Indonesian in the abstracts of students’ academic papers. The research was conducted using a qualitative descriptive method. The data sources consisted of five thesis abstracts from students in the Indonesian Language and Literature Education Program at Madura University. Data collection was carried out through documentation and note-taking techniques, while data analysis was conducted through the stages of identification, classification, description, and drawing conclusions. The results of the study indicate that various errors in the use of the Indonesian language are still found in the abstracts of students’ scientific papers. These errors include spelling errors, word usage errors, punctuation errors, and the use of ineffective sentences. The most prevalent errors found were spelling errors and word usage errors. The findings of this study indicate that students’ proficiency in using the Indonesian language when writing abstracts still needs improvement. Therefore, a better understanding of Indonesian language conventions, as well as greater attention to detail in the writing and editing of academic papers, is necessary to ensure that the resulting abstracts are of higher quality and meet academic writing standards.